The impact of revenue diversification on bank profitability and stability: Empirical evidence from South Asian countries - Shoaib Nisar; Ke Peng; Susheng Wang; Badar Nadeem Ashraf (International Journal of Financial Studies, 2018)
This paper is a contribution to the ongoing debate on the benefits and drawbacks of bank revenue diversification. Revenue diversification may benefit banks if diversified activities are inherently less risky and possess high returns, while it may hurt banks if diversified activities are more risky and have low returns. Analyzing a panel dataset of 200 commercial banks from all South Asian countries, we found that overall revenue diversification into non-interest income has a positive impact on the profitability and stability of South Asian commercial banks. We further observed that different types of non-interest income-generating activities have different impacts on bank performance and stability. While fees and commission incomes have a negative impact on the profitability and stability of South Asian commercial banks, other non-interest income has a positive impact. Our results imply that banks can benefit from revenue diversification if they diversify into specific types of non-interest income-generating activities. Our findings are robust and relevant to the use of alternative measures of revenue diversification, profitability and stability.
Keywords: G01; G21; G32; 330; revenue diversification; non-interest income; bank stability; South Asian banks